BIOGEOCHEMICAL FEATURES OF HYDROCARBONS IN CULTURED CYANOBACTERIA AND GREEN ALGAE FROM ANTARCTICA (17th Symposium on Polar Biology) - マツモト, ゲンキ; ヤマダ, サチコ; オオタニ, シュウジ; / ナガシマ, ヒデユキ; MATSUMOTO, Genki I.; YAMADA, Sachiko; OHTANI, Shuji; BROADY, Paul A.; NAGASHIMA, Hideyuki (National Institute of Polar Research, 1996)
P(論文) Hydrocarbons in cultured cyanobacteria (Lyngbya murrayi, Oscillatoria priestleyi, Phormidium foveolarum, Phormidium fragile, Phormidium frigidum, Phormidium laminosum, Phormidium priestleyi and Phormidium unicinatum) and green algae (Chlorella vulgaris, Chlorococcum sp., Cosmarium crenatum, Cosmarium speciosum, Cosmarium subcrenatum, Cosmarium sp. and a species of Chlorococcales) from Antarctica were analyzed by the use of a gas chromatograph-mass spectrometer to clarify their geochemical features and discuss their biogeochemical significance. Short-chain (<C_<20>) n-alkanes [n-C_<17:0> (total carbon numbers per molecule: number of double bonds)] and n-alkenes (n-C_<17:1>, n-C_<17:2>, n-C_<18:1> and/or n-C_<19:1>) were found in some cyanobacteria and green algae, but branched alkenes [(4-methyl-C_<18:1>, 3-methyl-C_<18:1>, 3-methyl-C_<18:2>, 4-methyl-C_<19:1>, 3-methyl-C_<19:1> and/or 3-methyl-C_<19:2>] were detected only in cyanobacteria (L. murrayi, P. fragile and/or P. laminosum). Phytadienes were the predominant hydrocarbons in a cyanobacterium (P. frigidum) and green algae (C. vulgaris, and 4 species of Cosmarium). The presence of long-chain (>C_<19>) n-alkanes and n-alkenes in some cyanobacteria and green algae strongly suggests that these organisms are important sources of long-chain (>C_<19>) hydrocarbons in sedimentary and soil environments of Antarctica. The abundance of alkenes in cyanobacteria (75.7-98.0%) and green algae (88.2-100%) is probably due to the cultured low incubation temperatures of cultures (10 or 15℃) and/or to adaptation to an extremely cold climate in Antarctica. The branched alkenes could be useful in chemotaxonomy of cyanobacteria. departmental bulletin paper